Overseas listing of China's companies : causes and consequences - Wu, Yujun (2008)
Examines the causes and consequences of the overseas listing decisions and explains why these firms would like to list on the overseas market, through a study of 72 Chinese firms listed in the Hong Kong Exchange and 663 domestically listed Chinese firms.